Elsie Piddock skips in her sleep - Farjeon, Eleanor, 1881-1965.; Voake, Charlotte (Somerville, Massachusetts : Candlewick Press, 2017)
Elsie Piddock has such a talent for rope skipping that he fairies on nearby Mount Caburn award her a magical rope and, may years later at the age of 109, Elie returns to skip again and save the mountain from the destructive plans of the greedy new owner.
Keywords: Rope skipping -- Juvenile fiction; Fairies -- Juvenile fiction; England -- Juvenile fiction; Fairies; Rope skipping; England; Fairy tales; Fiction; Juvenile works; Fairy tales